OPTIMASI ENERGI DENGAN IOT DAN FUZZY LOGIC PADA AC SMART DI GEDUNG DHARMA WACANA - Saputri, Tri Aristi; Sutomo, Budi; Hairunnisa, Afifah (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2024)
Efficient energy management in air conditioning (AC) systems is a critical challenge in the modern era, particularly in educational buildings such as Dharma Wacana Hall. This study aims to design and implement an Internet of Things (IoT)-based Smart Air Conditioning system utilizing fuzzy logic to optimize energy management. The system employs DHT22 sensors and ESP32 microcontrollers to monitor indoor and outdoor temperatures in real-time. The collected data were analyzed using the Mamdani fuzzy logic method, resulting in automated AC adjustments. Over a 29-day testing period, the system demonstrated its capability to adapt cooling intensity based on environmental conditions, achieving an average energy savings of 4% on moderate-temperature days. However, on days with higher cooling demands, energy consumption exceeded that of conventional systems. In conclusion, the system successfully improved energy efficiency and thermal comfort in educational buildings, although further development is needed to enhance sensor accuracy and system resilience to internet dependency. This research contributes to the application of IoT technologies for energy efficiency, particularly in the educational sector.